Estrategias de marketing digital en la isla del paseo shopping “El Guanabanazo” en la ciudad de Babahoyo en el periodo 2024. - Anchundia Miranda, Jaccely Melina (2025)
Investigating digital marketing strategies that help increase sales at GUANABANAZO in Babahoyo is the objective of the study. The inductive research method was used, which allows estimating the probability of creating a digital marketing strategy proposal to increase sales and at the same time generating broad conclusions on the topic through reasoning. Examining the characteristics and manifestations of a phenomenon allows us to analyze it in detail. On the other hand, field research gives us the invaluable opportunity to obtain data directly from reality without changing the events or places where they occur. This gives us a deep understanding of the real situations that the company faces in relation to its digital marketing initiatives. The goal of collecting data and administering surveys is to obtain accurate and complete information about the practices and knowledge that exist within the organization's digital domain. To "know what is happening, what the respondents think or what they think through written questions", techniques such as interviews and surveys are used to collect data. After carrying out the corresponding analysis, it is considered essential that the company uses digital marketing strategies through social networks. This is because these actions will strengthen the relationship with customers and, as a result, have a good positioning and increase profitability through an increase in sales.